REPRODUCTIVE BIOLOGY OF INDIAN SHAD (TENUALOSA ILISHA) IN THE BHAGIRATHI-HOOGHLY STRETCH OF RIVER GANGA - BHAUMIK, UTPAL; BOSE, SRITAMA; SATPATHY, B. B.; MANNA, R. K.; SAHOO, A. K.; ROSHITH, C. M. (Journal of the Inland Fisheries Society of India, 2021)
Hilsa (Tenualosa ilisha ) is a major fishery in the Bhagirathi-Hooghly river accounting for about 15-20% of total fish landings. It is an anadromous fish, which migrates to the Bhagirathi-Hooghly river system from the Bay of Bengal for breeding and spending their earlier part of life. Aspects like gonado-somatic, fecundity, maturity and breeding season were studied during 2011 and 2012. The gonado-somatic relation for male could not be drawn due to highly fluctuating values and for females it was y=8.837+0.004x. Fecundity ranged from 44,002 to 15, 54,894 in the size range of 208mm to 475mm and 105g to 1175.5g. The minimum fecundity value recorded was lowest ever recorded for the species. The first maturity size for males tallied with the previous record but the same was comparatively lower for the females. Breeding season varied with year and indicated linkage with the monsoon and intensity of flood. Key words : Tenualosa ilisha, gonado somatic index, fecundity, maturity, Ganga